ESSENTIAL OIL COMPOSITION AND ANTIOXIDANT ACTIVITY FROM ALPINIA SIAMENSIS K. SCHUM. RHIZOME - Theanphong, Orawan; Jenjittikul, Thaya; Mingvanish, Withawat (Interprofessional Journal of Health Sciences, 2023)
The chemical compositions of hydrodistilled essential oils from different ages of fresh rhizome of A. siamemsis (6 and 9 month) were analysed by GC-MS technique. 1, 8-Cineole was obtained as the main component in both essential oils (20.49 and 29.68%, respectively). The antioxidant activities of two essential oils were evaluated by DPPH radical scavenging, hydroxyl radical scavenging, ferrous ion chelating, superoxide anion radical scavenging and ferric reducing power assays. L-ascorbic acid and ethylenediaminetetraacetic acid (EDTA) were used as a positive control. The DPPH radical scavenging activity and ferric reducing power of both of essential oils and L-ascorbic acid were found to be insignificantly different whereas the hydroxyl radical scavenging activity of the 6-month rhizome essential oil was found to be significantly higher than the 9-month rhizome essential oil and L-ascorbic acid. The superoxide anion radical scavenging activities of the 6- and 9-month rhizome essential oils were found to be insignificantly different. However, the 9-month rhizome essential oil had much higher superoxide anion radical scavenging activity than L-ascorbic acid. Both of the essential oils showed less chelating activity for ferrous ions as compared with EDTA.